Signaling through estrogen receptors modulates long non-coding RNAs in prostate cancer. (1st July 2020) - Nanni, Simona; Bacci, Lorenza; Aiello, Aurora; Re, Agnese; Salis, Chiara; Grassi, Claudio; Pontecorvi, Alfredo; Gaetano, Carlo; Farsetti, Antonella
Abstract: Prostate cancer (PCa) is a sex-steroid hormone-dependent cancer in which estrogens play a critical role in both initiation and progression. Recently, several long non-coding RNAs (lncRNAs) have been associated with PCa and are supposedly playing a pivotal role in the biology and progression of this type of cancer. In this review, we focused on some lncRNAs that are known for their androgen and estrogen transcriptional responsiveness in PCa. Specifically, we summarized recent pieces of evidence about lncRNAs NEAT1, H19, MALAT1, and HOTAIR, in estrogen signaling, emphasizing their role in PCa progression and the acquisition of a castration-resistant phenotype. Here, the reader will find information about lncRNAs present in estrogen-dependent transcriptional complexes. The potential role of lncRNA/estrogen signaling as a novel pathway for PCa treatment will be discussed.